2020
DOI: 10.1038/s41598-020-62754-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations of C-reactive Protein with 25-hydroxyvitamin D in 24 Specific Diseases: A Cross-sectional Study from NHANES

Abstract: Most diseases might be associated with acute or chronic inflammation, and the role of vitamin D in diseases has been extensively explored in recent years. Thus, we examined the associations of one of the best markers for inflammation-C-reactive protein (CRP) with 25-hydroxyvitamin D [25(OH)D] in 24 specific diseases. We performed cross-sectional analyses among 9,809 subjects aged ≥18 years who participated in the U.S. National Health and Nutrition Examination Survey (NHANES) in 2007~2010. The generalized addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
9
1
1
Order By: Relevance
“…al. [92]. In particular, it consistently outperforms competing methods within the range of network sizes one tends to encounter in network analysis of macromolecular complexes (hundreds to thousands of nodes).…”
Section: Generalized Network Communities Within the Leurs : Trn A Leumentioning
confidence: 79%
“…al. [92]. In particular, it consistently outperforms competing methods within the range of network sizes one tends to encounter in network analysis of macromolecular complexes (hundreds to thousands of nodes).…”
Section: Generalized Network Communities Within the Leurs : Trn A Leumentioning
confidence: 79%
“…The strength and the directionality of the associations between vitamin D and CRP appears to differ by conditions, and it is not always linear [68,69]. One study reported a strong inverse association between vitamin D and CRP in individuals with inflammatory diseases (acute and chronic) compared to non-inflammatory diseases (β −0.879 vs. −0.499) [69].…”
Section: Vitamin D Omega 6:3 Ratio and Crpmentioning
confidence: 99%
“… It is well established that serum CRP and 25[OH]D levels are inversely correlated, as would be expected if 25[OH]D were a negative acute phase reactant. 6 , 7 Low blood levels of 25[OH]D are associated with numerous medical conditions consonant with metabolic stress, including preeclampsia, autoimmune disorders, infectious diseases, cardiovascular disease, cancers, type 2 diabetes, subcutaneous and visceral adiposity and obesity, neurological disorders, acute pancreatitis, and a variety of other inflammatory states. 8 , 9 These findings have generally been interpreted to indicate that deficiency of vitamin D predisposes to or aggravates those conditions, rather than considering the possibility that it is the conditions themselves that lead to a low 25[OH]D level – a classic chicken and egg conundrum.…”
Section: Evidence That Vitamin D Is a Negative Acute Phase Reactantmentioning
confidence: 99%
“…It is well established that serum CRP and 25[OH]D levels are inversely correlated, as would be expected if 25[OH]D were a negative acute phase reactant. 6 , 7 …”
Section: Evidence That Vitamin D Is a Negative Acute Phase Reactantmentioning
confidence: 99%